2012
DOI: 10.1002/ase.1273
|View full text |Cite
|
Sign up to set email alerts
|

Learning surgically oriented anatomy in a student‐run extracurricular club: An education through recreation initiative

Abstract: Didactic and laboratory anatomical education have seen significant reductions in the medical school curriculum due, in part, to the current shift from basic science to more clinically based teaching in North American medical schools. In order to increase medical student exposure to anatomy, with clinical applicability, a student‐run initiative called surgically oriented anatomy prosectors (SOAP) club was created within the extracurricular program at the Schulich School of Medicine and Dentistry, The University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Comparable clinical anatomy teaching approaches have been implemented in Germany (Pabst et al, ; Peuker et al, ; Boeckers et al, ), United States (Drake, ; Are et al, ; Haubert et al, ; Ullah et al ; Tocco et al, ), and Australia (Burgess and Ramsey‐Stewart, ). Reinhard Pabst from Medical School in Hannover was the first in Germany to supplement a dissection course with living anatomy, X‐ray anatomy, patient presentations, and films on clinical problems (Pabst et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable clinical anatomy teaching approaches have been implemented in Germany (Pabst et al, ; Peuker et al, ; Boeckers et al, ), United States (Drake, ; Are et al, ; Haubert et al, ; Ullah et al ; Tocco et al, ), and Australia (Burgess and Ramsey‐Stewart, ). Reinhard Pabst from Medical School in Hannover was the first in Germany to supplement a dissection course with living anatomy, X‐ray anatomy, patient presentations, and films on clinical problems (Pabst et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the TSC, these lessons were held as weekly seminars with anatomical prosections of specially dissected specimens, and, moreover, focused on practical procedures (knee joint examination, nose endoscopy) (Peuker et al, ). At the Schulich School of Medicine and Dentistry in Ontario, Canada, surgeons were invited by a student surgical club to demonstrate surgical procedures to medical students (Ullah et al, ). The surgical setup and demonstrated procedures may have been similar to those in the TSC, and the small group size should have been more beneficial with regards to the learning atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The focus group and questionnaire results of the current study revealed that the CST2 trainees in the LPSS found teaching anatomy to medical and other students to be valuable for improving their own anatomy knowledge, and hence a positive contribution to their overall surgical training, especially as it was not limited to gross anatomy. Anatomy education and medical education in general has changed in recent years, and in some institutions, this has meant the decision to teach anatomy without human cadavers (Willan, ; Older, ; Hanna and Tang, ; Ullah et al, ). The results of the current study have shown anatomy demonstrating using cadavers to be of benefit to trainees, and the opportunity to teach anatomy was one of the reasons that trainees applied to join the London Core Surgical Training Program.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al described student-organized half-day workshops known as "Surgery Saturday" (for first-and second-year medical students), in which surgical faculty introduced students to suturing, knot tying, open instrument identification, operating room etiquette, and basic laparoscopic skills (Patel et al, 2013). Similarly, Ullah et al described student-organized extracurricular Surgically Oriented Anatomy Prosectors (SOAP) club meetings, during which surgeons demonstrated surgical procedures on cadavers (Ullah et al, 2012). The University of Cape Town Surgical Society described by Leusink and Hoffmnan (2012) is also a student-run society that promotes medical and surgical research in order to motivate undergraduate medical students to pursue a career in surgery.…”
Section: Student Surgical Interest Groups and Surgical Competitionsmentioning
confidence: 98%